The Alteration Level of VEGF of Colon Cancer Cell After Induction with Mandarin Orange (Citrus Reticulata) Peel Ethanol Extract - Astuti, Yoni; Zuliana Utami, Anisa; Suharto, Agus; Yano, Yoshihiko; Aristyaning Putri, Wahyu (Biosaintifika: Journal of Biology & Biology Education, 2024)
The natural ingredient-based therapy extracted from various plants is assumed more tolerable to cancer patients’ bodies than synthetic drugs. To tell successful novel cancer therapy, an indicator is needed to confirm the result. VEGF is a pro-angiogenic factor that leads the cancer cells’ invasion to another organ and is associated with high mortality in patients. Hence, the VEGF level is widely used as one of the successful cancer therapy indicators. Purposed of research elucidated the effect of Mandarin orange peel ethanol extract (EEKJM) to improve the reduction of VEGF levels in colon cancer in vitro. This study was an experimental posttest and control group design to analyze different level of VEGF on cancer cells at end of the study.  Research began with the preparation of EEKJM followed by a cytotoxic extract test using the MTT assay method. Furthermore, the measurement of VEGF levels by the VEGF ELISA kit protocol. One Way ANOVA was performed to analyze data.Results showed the cytotoxic test of the EEKJM and doxorubicin against WiDr cells was 240 g/ml and 1.59 µg/ml. VEGF levels showed decreasing after being induced with EEKJM and doxorubicin with doses ½ IC50 and ¼ IC50. Conclusion: EEKJM was able to reduce VEGF levels and viability of WiDr colon cancer cells. The advantages are as much as initial evidence of the ability of the orange to treat cancer even though further animal studies or evidence of a pathway of decrease of the VEGF or other signals are required.